"Studies in human rights/ edited by V. T. Patil and T. S. N. Sastry," - "Patil, V. T. (ed.)" (Pondicherry, 2000)
In the saga of struggle between liberty of man and the authority of the State, after many centuries the natural or human rights of the individual have become an intrinsic part of contemporary civilization. Initially, human rights were conceived in the limited context of freedom from arbitrary or totalitarian forms of government. With the advent of democracy and constitutional government the constitutions of various countries provided for guarantee of individual liberty or protection against the arbitrary acts of the State. However, well-meaning these national efforts for appropriate codification of the fundamental freedoms of the individual, the fact was that these attempts remained unsatisfactory, half-hearted, inadequate and perfunctory since consensus of the international community was not forthcoming on the question of adequate protection against the authority of the modern interventionist State.
Keywords: Civil rights